Microstructural evolutions of Sn-3.0Ag-0.5Cu solder joints during thermal cycling. (April 2018) - Libot, J.B.; Alexis, J.; Dalverny, O.; Arnaud, L.; Milesi, P.; Dulondel, F.
Abstract: Temperature-induced solder joint fatigue is a main reliability concern for aerospace and military industries whose electronic equipment used in the field is required to remain functional under harsh loadings. Due to the RoHS directive which eventually will prevent lead from being utilized in electronic systems, there is a need for a better understanding of lead-free thermomechanical behavior when subjected to temperature variations. As solder joints mechanical properties are dependent of their microstructural characteristics, developing accurate solder joint fatigue models means to correctly capture the microstructural changes that undergo the solder alloy during thermal cycling. This study reports the Sn3.0Ag0.5Cu (SAC305) solder joints microstructural evolution during damaging temperature cycles. Electron BackScatter Diffraction (EBSD) analysis was conducted to assess the SAC305 microstructure corresponding to a specific damage level. Investigated microstructural features included the β-Sn grain size and crystallographic orientation, as well as the grain boundary misorientation and Ag3 Sn intermetallic compound (IMC) size. As-reflowed and damaged components were also mechanically characterized using nanoindentation technique. The microstructural analysis of SAC305 solder joints prior to thermal cycling showed a highly textured microstructure characteristic of hexa-cyclic twinning with two β-Sn morphologies consisting of preferentially orientated macrograins known as Kara's beach ball, along with smaller interlaced grains. The main observation is that recrystallization systematically occurred in SAC305 solder joints during thermal cycling, creating a high population of misoriented grain boundaries leading to intergranular crack initiation and propagation in the high strain regions. The recrystallization process is accompanied with a progressive loss of crystallographic texture and twinning structure. Ag3 Sn IMCs coalescence is another strong indicator of SAC305 solder damage since the bigger and more spaced the IMCs are the less dislocation pinning can prevent recrystallization from occurring. Highlights: Recrystallization phenomenon is observed in the most deformed region of the solder joint, There is a loss of crystallographic texture during thermal cycling-induced damage, The interlaced morphology is never observed on damaged solder joints, Smaller recrystallized β-Sn grains (≈2 μm) are observed along the crack path, Recrystallized grains exhibit a lower hardness compared to the rest of the solder interconnect.